ACIDIZING EVALUATION OF CARBONATE ROCK IN BDA-F WELL, JATIBARANG FIELD - Widyanata, Andri; AM, Suranto; Suhascaryo, Nur (Journal of Petroleum and Geothermal Technology, 2023)
Acidizing is a dissolving activity, whether it is dissolving rock formations or other materials (natural or foreign) in reservoir of the rock. To maintain production in the Jatibarang field, especially in Bangodua (BDA) structure, there are 1 well that have experienced a short decline in production since drilling. The reservoir properties of that well is not good and there is impurity material (damage). Thus, requiring stimulation in the form of matrix acidizing. Evaluation of the matrix acid work in this well, is required for the same activities in other wells.To restore productivity this well, data were collected starting from production data, reservoir data, and well composition data. Then, candidate analysis and matrix acidizing job design are carried out. The design stage will be brought to the execution of matrix acidizing in the field. Then an evaluation was carried out after the presence of matrix acidizing in this wellThis well carried out matrix acidizing activities, produced oil production gains. BDA-F well produced with artificial lift of Electrical submersible pump – ESP in C1 layer (1128 – 1130.5 mMD), experienced an increase in test production from 749 BLPD to 1865 BLPD with a decrease in skin factor from +32 to -1.